Situating relevance: exploring individual relevance assessments in context - Theresa Dirndorfer Anderson (Information Research: An International Electronic Journal)
This paper discusses some of the challenges encountered whilst researching and writing a thesis that explores individual understandings of relevance and topic. It is based upon a discussion paper and presentation prepared as part of the Doctoral Workshop held during the ISIC 2000 Conference in Borås, Sweden. The focus of this paper is the doing of qualitative research. To provide a framework for this discussion, the key assumptions that have shaped the author's thesis are presented in the first section of this paper. The paper then focuses on some of the dilemmas of qualitative research encountered during the research and writing of this thesis, giving particular attention to the notion of context and the writing of qualitative research. Forthcoming results from the thesis are mentioned in the closing section. A Thesis Summary is also provided at the end of this paper.